The impact of climate change on medicinal plants and natural products: A scoping review - Takubessi, Marce Inggritha; Jalil, Banaz; Heinrich, Michael (Frontiers in Pharmacology, 2025)
BackgroundMedicinal plants and natural products are essential for healthcare systems globally, and, at the same time, they are a part of ecosystems and have major socioeconomic importance in many regions of the world. However, climate change has threatened their supply and sustainability. In this review, we map the current state of research on how climate change affects medicinal plants, focusing on ecological shifts, traditional uses, changes in bioactive metabolites, and adaptation strategies.MethodsThis scoping review, which was conducted following the PRISMA-ScR guidelines, involved comprehensive searches in PubMed, Scopus, and Web of Science of studies published between 2004 and 2024. Data were extracted to summarize study characteristics, climate change factors, species distribution, bioactive metabolites and marker compounds variations, and healthcare implications.ResultsA total of 219 studies were included, showing a significant increase in publication after 2021. Most studies were conducted in Asia, especially in China and India, whereas Europe, Africa, and South America remain underrepresented. The review covers 367 medicinal plant species, including high-altitude, climate-sensitive species such as Nardostachys jatamansi and Paris polyphylla. Of these, 40.6% are classified as threatened by the IUCN, and 59.4% remain unevaluated, which shows significant conservation gaps. Research methods have evolved from basic experiments to advanced computational approaches, notably species distribution modeling (SDM), with MaxEnt being the most widely used. Although climate change is projected to increase habitat suitability for 70 species, it has also led to a decline in suitable habitats for 106 species, range shifts in 94 species, and placed 33 species at the risk of extinction and habitat loss. The ecological changes also impact traditional accessibility and the reliability of medicinal plant-based therapies. Moreover, shifts in bioactive metabolite production, including both increases and decreases, are linked to several environmental factors, such as rising temperatures, elevated CO2, reduced precipitation, and drought stress.ConclusionClimate change is reshaping the ecology and pharmacological value of medicinal plants. Although adaptation strategies exist, their implementation remains limited. An interdisciplinary, coordinated response is urgently needed to ensure sustainable production and use. This will also require a paradigm shift in all aspects of ethnopharmacological research and development.